Fibroblasts as a ruler of the immune microenvironment: measurement and modulation in tissue homeostasis and disease - Zhang, Yanling; Fang, Xinyi; Yan, Lian; Wang, Lin (Frontiers in Immunology, 2026)
Fibroblasts, once considered merely passive structural components of tissues, are now recognized as dynamic regulators of the immune microenvironment. Recent advances in single-cell and spatial multi-omics have revealed their profound heterogeneity, spatial organization, and functional plasticity, positioning them as a ‘ruler’ that measures, defines, and shapes local immune responses. In both homeostasis and disease contexts—such as cancer, autoimmune disorders, and fibrosis—distinct fibroblast subpopulations exhibit specialized roles: some drive immunosuppression via PD-L1 expression, TGF-β secretion, or metabolic reprogramming; others promote inflammation or fibrosis through cytokine and chemokine secretion; while a subset supports immune resolution and tissue repair. Spatially, fibroblasts organize immune territories by forming physical and chemical barriers, orchestrating tertiary lymphoid structures, and partitioning inflammatory zones. Their bidirectional crosstalk with immune cells—including T cells, macrophages, and B cells—further fine-tunes immune activation or suppression. The dysregulation of fibroblast subsets is a hallmark of disease progression and therapy resistance. Emerging therapeutic strategies aim to ‘recalibrate’ this dysfunctional ruler through targeted depletion, phenotypic reprogramming, or disruption of pathogenic signaling. Integrating fibroblast-centric metrics into clinical practice may enable precise assessment of the immune microenvironment and personalized interventions, heralding a new era in immunotherapy and fibrotic disease management.